EU regulation of e-commerce : a commentary - Lodder, Arno R.; Murray, Andrew D. (Elgar commentaries series, 2022)
"Significantly revised and expanded, this important book addresses the key pieces of EU legislation in the field of e-commerce, including on consumer rights, copyright, electronic identification, open internet access, electronic payments, competition law and digital content. Key features of this second edition include: - thoroughly up-to-date analysis of decisions of the Court of Justice and the Commission - article-by-article commentary on the latest directives and regulations in the field of e-commerce - a unique structure featuring detailed tables of cases and legislation and paragraph references, enabling easy access to all substantive legal provisions - new chapters featuring analysis of services in the internal market, copyright in the Digital Single market, measures concerning open internet access and more. This unique work provides an updated account of the essential pieces of EU legislation on e-commerce. Legal practitioners will benefit from the clear structure and close examination of key provisions. The book will also appeal to legal scholars and advanced students, who will appreciate the concise overview and thoughtful analysis on future developments in the field"--